Local content and sustainable development in global energy markets - Olawuyi, Damilola S. (New York Cambridge University Press, 2021)
Energy is inextricably linked to all aspects of human life: the ability to work, live, survive, and execute tasks. Given the significance of energy to human life and the global economy, global energy markets are rapidly growing and have witnessed significant transformations over the last few decades
Includes index.
Keywords: Energy consumption--Law and legislation